Parameters (σ, ε) of Lennard-Jones for Fe, Ni, Pb for Potential and Cr based on Melting Point Values Using the Molecular Dynamics Method of the Lammps Program. (March 2020) - Maghfiroh, C Y; Arkundato, A; Misto,; Maulina, W
Abstract: Lennard-Jones potential is the potential energy of the bond interaction between two atoms or free molecules based on the distance between them. Molecular dynamics simulations can be used to calculate various physical properties of materials based on specific interaction potentials. One of the physical properties of a material is its melting point. This research was conducted to find the potential parameter values of Lennard-Jones metal Fe, Pb, Ni and Cr based on the melting point value of the material using the LAMMPS program. In this study the normalization of potential parameters is done by comparing the results of the simulation melting point with the experimental melting point. This research produces a Lennard-Jones potential parameter value which yields a melting point value that has a relatively small description.